Religious moderation values in al Islam and kemuhammadiyahan textbooks at high school level - Arofi, Muhammad Zuhron; Pratiwi, Eko Kurniasih; Arofi, Nasitotul Janah; Ridwan, Wachid (UIN Salatiga, 2024)
After being launched by the Ministry of Religion in 2019, the concept of religious moderation continues to gain public attention. It can be seen from the large amount of research regarding religious moderation which is embedded in many objects. This research took the material and curriculum objects of Al Islam and Kemuhammadiyahan (AIK) which are taught in Muhammadiyah schools at the high school level. This research aims to determine the value of religious moderation in AIK textbooks. This study was qualitative research with a content analysis approach. The first step of this study was collecting journals, reference books related to religious moderation, and textbooks used for the teaching and learning process in Muhammadiyah schools. Following the first step, analysis was conducted to describe the concept inside the source books. The conclusion was made then. The findings showed that there were several important points in AIK textbooks that align with the spirit of moderation. These points were ukhuwah (brotherhood), non-violence, tolerance, and commitment to nationality.